STRATEGI KOMUNIKASI DALAM MENINGKATKAN PUBLIC SPEAKING PADA KARYAWAN ALFADH PARFUM - Ariftha, Annisa (NIVEDANA : Jurnal Komunikasi dan Bahasa, 2023)
This research investigates effective communication strategies in improving the public speaking skills of Alfadh Parfum employees. In the competitive business world, public speaking ability is a very important skill for companies like Alfadh Parfum. This study uses a qualitative and quantitative approach, collecting data through in-depth interviews and structured surveys from employees who took part in the company's public speaking training program. The research results show that an integrated approach involving intensive training, simulation practice sessions, and direct feedback from trainers and colleagues is very effective in improving public speaking skills. Additionally, the implementation of communications technology such as video conferencing platforms enables remote training, allowing employees to participate without geographic restrictions. This approach not only helps overcome public speaking anxiety but also strengthens self-confidence and the ability to convey messages clearly. This research underlines the importance of targeted and integrated communication strategies in improving public speaking, producing Alfadh Parfum employees who are more confident, effective and charming in communicating with various parties, which ultimately improves the company's reputation.